Arguments in the debate austerity versus growth in Romania - Bogdan Andrei Dumitrescu (Romanian Journal of Fiscal Policy (RJFP), 2015)
The fiscal policy response to the consequences of the financial and economic crisis consisted either in adopting expansionary policies to stimulate the aggregate demand, or in promoting fiscal consolidation programs designed to restore the sustainability of the public finances. This paper examines the options of the Romanian authorities regarding the fiscal policy decisions in the immediate aftermath of the crisis, and subsequently as the fiscal consolidation program initiated in 2010 has advanced. The paper concludes that the advantages and disadvantages of both approaches cannot be analyzed without taking into account the short-term constraints and the solution adopted by the policymakers, namely to realize the fiscal adjustment was inevitable.
Keywords: E62; H12; H60; 330; fiscal consolidation; economic growth; crisis management